2018
DOI: 10.1590/2179-8087.060517
|View full text |Cite
|
Sign up to set email alerts
|

Soil Influences on Tree Species Distribution in a Rupestrian Cerrado Area

Abstract: This study aimed to analyze relations between the distribution of tree species and variations in soil texture, fertility and organic matter levels in a rupestrian cerrado area located in Diamantina-MG. Individual trees with circumference at soil level (PC) ≥ 3 cm were sampled in 10 plots of 20x50m. Samples of surface soil (0.00-0.20 m of depth) were collected from each plot and analyzed for their chemical and physical properties. Through canonical correspondence analysis, Eremanthus incanus, Kielmeyera lathrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The ten species with the highest value in use were: Terminalia fagifolia Mart (Rama branca) was indicated by the community for civil construction, serving as fence, rafters in the construction of houses and in the production of energy, using it as firewood in domestic activities. This use can be attributed to its wood presenting density of 1.00 g/cm³, and hard to be cut [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ten species with the highest value in use were: Terminalia fagifolia Mart (Rama branca) was indicated by the community for civil construction, serving as fence, rafters in the construction of houses and in the production of energy, using it as firewood in domestic activities. This use can be attributed to its wood presenting density of 1.00 g/cm³, and hard to be cut [25].…”
Section: Resultsmentioning
confidence: 99%
“…ex Hayne, (Jabotá) was cited for the construction of house roofs, serving as slats and rafters. This is because species of this genus are considered highly resistant to termites and fungi of white and brown rot, the apparent specific mass of this genus 960 kg/m³ [25].…”
Section: Resultsmentioning
confidence: 99%
“…On the northern side, there is a mature eucalyptus stand (15 years old) consisting of trees with an average diameter of 23 cm and an average height of 25 m. This eucalyptus stand may explain the greater amount of carbon in the soil on the northern side due to biomass recycling and litter deposition, influencing not only the increase of in the amount of carbon but also nutrients cycling (Wink et al, 2018), which is essential for the growth and increment of vegetation. Dantas et al (2018), when analyzing the influence of soil on the distribution of tree species in the Cerrado, observed that soil organic matter influences the distribution of species and the number of trees. This finding explains the gradient also observed in the tree carbon stock.…”
Section: Spatial Analysismentioning
confidence: 99%
“…We have assumed in this work that (1) the environmental heterogeneity is one of the most important factors to determine species gradient richness (Stein et al, 2014); (2) the rupestrian environments present heterogeneous environmental conditions (Abadia, Lenza, et al, 2018; Schaefer et al, 2016), with rocky outcrops, making them suitable habitat for various species (Abadia et al, 2023; Lemos et al, 2013; Lenza et al, 2011); and (3) a low soil depth, water scarcity and low nutrient availability (Alho et al, 2007; Benites et al, 2007; Messias et al, 2013; Schaefer et al, 2016) can limit species establishment and individual development (Abreu et al, 2012; H. A. Almeida et al, 2018; Dantas et al, 2018). Based on such assumptions, we tested the following hypotheses: (1) the RCEL presents a higher richness of shrub‐tree species compared to the TCRO and the TCEQ due to a greater environmental heterogeneity (micro‐habitats), with increased niche availability and the occurrence possibility among species (Abadia, Lenza, et al, 2018; Adler et al, 2013); and (2) shrub‐tree species in the RCEL present lower SLA and FNC values because of the limiting conditions (de Cássia‐Silva et al, 2017; Maracahipes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(2) the rupestrian environments present heterogeneous environmental conditions (Abadia, Lenza, et al, 2018;Schaefer et al, 2016), with rocky outcrops, making them suitable habitat for various species (Abadia et al, 2023;Lemos et al, 2013;Lenza et al, 2011); and (3) a low soil depth, water scarcity and low nutrient availability (Alho et al, 2007;Benites et al, 2007;Messias et al, 2013;Schaefer et al, 2016) can limit species establishment and individual development (Abreu et al, 2012;H. A. Almeida et al, 2018;Dantas et al, 2018). Based on such assumptions, we tested the following hypotheses:…”
Section: Introductionmentioning
confidence: 99%